Physical Activity Mediates the Relationship between Gait Function and Fall Incidence after Total Knee Arthroplasty - Taniguchi, Masashi; Sawano, Shinichiro; Maegawa, Shoji; Ikezoe, Tome; Ichihashi, Noriaki (The Journal of Knee Surgery, 2020)
The present study aims to examine (1) the preoperative factors that can predict postoperative falls, (2) whether postoperative physical activity (PA) mediates the relationship between fall incidence and gait function, and (3) whether postoperative PA levels are associated with fall risk in total knee arthroplasty (TKA) patients. Ninety-six patients (mean age: 72.0 ± 6.1 years) who were observed postoperatively for 6 months were selected. Timed up and go (TUG) was assessed as an indicator of gait function. Fall incidence and PA were investigated for 6 months post-TKA. The body mass index, history of preoperative falls, knee pain, knee extensor strength, range of motion in knee flexion, and modified gait efficacy scale were evaluated. Additionally, postoperative PA levels were categorized into three groups—low: <3,000, moderate: 3,000 to 4,000, and high: ≥4,000 steps/day. The relative fall incidence rate was calculated according to the total number of falls normalized for every 1,000 steps/day for 6 months postoperatively. Twenty-five (26.0%) of the 96 patients had at least one fall. The TUG, knee pain, and knee extensor strength were identified preoperatively as significant variables affecting postoperative falls. The mediated effects model revealed that postoperative fall incidence was predicted by preoperative TUG and postoperative PA. Postoperative PA was significantly associated with preoperative TUG. Moreover, both the preoperative TUG and postoperative PA were selected as significant variables for predicting fall incidence. Thus, postoperative PA mediates the relationship between gait function and fall incidence after TKA. Furthermore, the relative fall incidence rate associated with a low PA level was significantly higher than that associated with moderate and high PA levels. In conclusion, preoperative assessments of TUG performance, muscle strength, and knee pain were effective in predicting fall risk. Additionally, an increase in PA could contribute to reducing fall risk in TKA patients. Therefore, our results suggest that preoperative screening for fall predictors and managing postoperative PA could reduce the fall incidence in TKA patients.
Keywords: physical activity; fall incidence; gait function; total knee arthroplasty